EVALUASI PENERIMAAN PENGGUNA BKD (BEBAN KERJA DOSEN) ONLINE PADA UIN SYARIF HIDAYATULLAH JAKARTA DENGAN MENGGUNAKAN METODE UTAUT - Fitroh Fitroh (STUDIA INFORMATIKA: JURNAL SISTEM INFORMASI, 2016)
BKD online application UIN Syarif Hidayatullah Jakarta is an application used by lecturers to report performance results Tri Dharma College. In the process of user acceptance of these applications, the researchers intend to conduct an evaluation using UTAUT (Unified Theory of Acceptance And Use of Technology) where in the method UTAUT conducted the testing process of hypothesis that H1 (performance expectancy), H2 (effort expectancy), H3 (social influence), H4 (Facilitating conditions) should be in signifikasikan with variable BI (Behavioral Intention). In the study using questionnaires distributed to faculty at random. The results of the questionnaire are then processed to test the validity and reliability, the classic assumption test and multiple linear regression. Based on the results of testing standards are known to be larger (<) of 0.05. In the course of the work of researchers using the tools IBM SPSS 22 and Microsoft Excel. The results of this study are variable effort expectancy and facilitating conditions positively influence user acceptance BKD online application. While the effort expectancy proved significant because it allows the users of the system in the process of filling online application BKD. Performance Expectancy not significant for BKDonline application is merely a tool in faculty performance report and not a determinant of the performance of Tri Dharma College.